Potencial de escorrentía en función del número de curva en una cuenca serrana, Napostá Grande (Argentina) - López, Natalia (2023)
Knowledge of the runoff potential of a watershed is essential for short-and long-term water management and for socio-political and environmental decision-making. The simplicity of the NCRS-CN model makes it a useful tool in basins with absence of continuous hydrological records. The validation and adjustment of the CN in gauged basins provides greater reliability and transferability to the method. CN values were obtained by spatially weighted approximations, CNc, and by event-response analysis, SII and asymptotic methods. The CNs were validated on historical precipitation-runoff records considering event (short term) and cumulated (long term) series for two sub-basins with areal diversity, B1 and B2, of the Napostá Grande stream, Argentina. An adjustment to the hydrological reality of the basin was also evaluated. The SII method yields better results than the asymptotic and the CNc approximations for short-term analysis within both sub-basins, while on the long-term, annual or multi-year cumulative analysis, the adjusted CN is more representative for both B1 and B2. The models yielded herein constitute a deterministic mathematical representation that would allow predicting runoff from precipitation data, and their use can be extrapolated to ungauged regional basins with areal diversity.